The High Sierra : a love story - Robinson, Kim Stanley (Little, Brown and Company, 2022)
"Kim Stanley Robinson first ventured into the Sierra Nevada mountains during the summer of 1973. He returned from that encounter a changed man, awed by a landscape that made him feel as if he were simultaneously strolling through an art museum and scrambling on a jungle gym like an energized child. He has returned to the mountains throughout his life--more than a hundred trips--and has gathered a vast store of knowledge about them. The High Sierra is his celebration of this exceptional range and an exploration of what makes this span of mountains one of the most compelling places on Earth." --